Aspirin Attenuates Cardiac Allograft Rejection by Inhibiting the Maturation of Dendritic Cells via the NF-κB Signaling Pathway - Zhang, Xi; Chang, Aie; Zou, Yanqiang; Xu, Heng; Cui, Jikai; Chen, Zhang; Li, Yuan; Du, Yifan; Wu, Jie; Yu, Jizhang; Du, Xinling (Frontiers in Pharmacology, 2021)
Background. Dendritic cells (DCs) serve as an important part of the immune system and play a dual-role in immune response. Mature DCs can initiate immune response, while immature or semi-mature DCs induce immune hyporesponsiveness or tolerance. Previous studies have shown that aspirin can effectively inhibited the maturation of DCs. However, the protective effect of aspirin on acute cardiac allograft rejection has not been studied. The aim of this study is to elucidate the effect of aspirin exert on allograft rejection. Methods. The model of MHC-mismatched (BALB/c to B6 mice) heterotopic heart transplantation was established and administered intraperitoneal injection with aspirin. The severity of allograft rejection, transcriptional levels of cytokines, and characteristics of immune cells were assessed. Bone marrow derived dendritic cells (BMDCs) were generated with or without aspirin. The function of DCs was determined via mixed lymphocyte reaction (MLR). The signaling pathway of DCs was detected by western blotting. Results. Aspirin significantly prolonged the survival of cardiac allograft in mouse, inhibited the production of pro-inflammatory cytokines and the differentiation of effector T cells (Th1, Th17), as well as promoted the regulatory T cells (Treg). The maturation of DCs in spleen was obviously suppressed with aspirin treatment. In vitro, aspirin decreased the activation of NF-κB signaling and the costimulatory molecules (MHCII, CD80, CD86, CD40) expression of DCs. Moreover, the pro-inflammatory cytokines and function of DCs were both suppressed by aspirin. Conclusions. Aspirin inhibits the maturation of DCs through NF-κB signaling pathway and attenuates acute cardiac allograft rejection.